Investigation of the physical-geographical characteristics of river delta with geophysical and satellite data. The case study of Pineios River, Greece - Mitsika, Georgia S.; Alexopoulos, John D.; Vassilakis, Emmanuel; Dilalos, Spyridon; Poulos, Serafim E. (MethodsX, 2023)
This paper presents the methodology of an applied geophysical and remote sensing research at river deltas for their subsurface and surface structure and its application in the deltaic plain of Pineios River (Thessaly, Greece). The scope is to primarily calculate the thickness of deltaic post alpine deposits, with the contribution of Transient Electromagnetic Method (TEM), but also identify the surficial characteristics (biotic/ abiotic) of the area with the appropriate combination of spectral bands and spectral indices. Regarding the remote sensing approach, some geomorphological features were outlined. This was managed from six false color composites of the area, produced by combining spectral bands and additional five false color composites by combining several spectral indices. •The results of the TEM method along with their statistical analysis provided important information regarding the spatial distribution and thickness of the lithological units along the deltaic plain.•The combination of spectral bands 8, 7, 6 seems to adumbrate the hydrographic network of the area and even detects possible changes in the inflow.•The combination of spectral indices MSAVI2, WV-BI, WV-WI was helpful enough to geomorphological mapping of the deltaic plain.
Keywords: Band ratios; Multispectral processing; Subsurface investigation; TEM method; Worldview-2